A Study on the Impact of the Fed’s Quantitative Easing Policy on the RMB Exchange Rate - Huang, Yulin (International Journal of Global Economics and Management, 2024)
In the context of global economic integration, the United States, as a major world economic power, the adjustment and change of its monetary policy is of great significance to the fluctuation of the RMB exchange rate. By studying the characteristics of the Fed’s QE (quantitative easing) monetary policy, this paper analyses its impact on international capital flows and trade markets, and describes how these impacts are transmitted to China’s currency market, causing fluctuations in the RMB exchange rate.